In vitro and in situ evaluation of Guasimo (Guazuma ulmifolia) and Cubato (Acacia cochliacantha) fruits - Sánchez-Santillán, Paulino; Herrera-Pérez, Jerónimo; González-Álvarez, Vicente Homero; Ayala-Monter, Marcó Antonio; Martínez-Martínez, Ricardo; Torres-Salado, Nicolás (Ecosistemas y Recursos Agropecuarios, 2025)
The fruits of dry tropical tree species such as Guasimo (Guazuma ulmifolia) and Cubato (Acacia cochliacantha) represent local alternatives for ruminant supplementation. The objective was to evaluate the production and composition of biogas in vitro and the in situ digestibility of these fruits. Dehydrated samples of both fruits were incubated in biodigesters to measure biogas production for 72 h of incubation in a closed system. In situ digestibility was by fermenting poly-silk bags in the rumen of two fistulated cows for 72 h and with these values the kinetics were estimated. The experimental design was completely randomized. The results showed that the production and composition of biogas did not present differences between fruits (P > 0.05); however, Guasimo presented higher in situ digestibility in the measured times (P ≤ 0.05), fast digestibility fraction and speed at which the potentially digestible fraction. In conclusion, Guasimo showed better rumen utilization, so it can be considered an efficient option as a forage supplement in tropical regions.